Penggunaan Model Pembelajaran Cooperatif Integrated Reading Compotition (CIRC) Dalam Pembelajaran Mahārah Qirā’ah di Kelas X MA Tarbiyatul Islam Soko Tuban Tahun 2023/2024 - Iqbal, Deny; Rohman, M. Fathor; Rosikh, Fahrur (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2024)
Arabic language lessons are mandatory lessons at MA Tarbiyatul Islam Soko. Based on the results of interviews and observations, one of the causes of students' difficulties in Arabic language lessons is their previous school background, this is what underlies teachers using the Cooperative Integrated Reading and Composition (CIRC) learning model so that learning can be achieved. includes all students who have different Mahārah Qirā'ah abilities. This research aims to observe and explain how the application, advantages and disadvantages of the Cooperative Integrated Reading and Composition (CIRC) model in Arabic language lessons, and how students' abilities in mahārah qirā'ah skills are, after the teacher applies the Cooperative Integrated Reading and Composition (CIRC) model. The research method used is qualitative research with the data collection process using interviews with school principal respondents, Arabic teachers and class x students. Observation during learning, and Documentation. Data analysis uses data reduction from interviews, observations and documentation, data display by presenting research data, and verification by analyzing data according to the problem formulation. Checking the validity of the data uses the credibility test, transferability test, debendability test, confirmability test. From the research that has been carried out, the following results were obtained; The Cooperative Integrated Reading and Composition learning model is used in Arabic language learning. The steps in its use are the teacher reading the material, dividing students into groups consisting of 4-5 students, students discussing with the group, students presenting the results of group work, teacher and students making conclusions. This learning model also has advantages and disadvantages. Students' Mahārah qirā'ah abilities obtained after learning are oral reading well and correctly, reading comprehension, and developing reading into writing